Neuromelanin Modulates Heterocyclic Aromatic Amine-Induced Dopaminergic Neurotoxicity - Lawana, Vivek (Toxicol Sci, 2020)
Heterocyclic aromatic amines (HAAs) are mutagens and potential human carcinogens. Our group and others have demonstrated that HAAs may also produce selective dopaminergic neurotoxicity, potentially relevant to Parkinson’s disease (PD). The goal of this study was to elucidate mechanisms of HAA-induced neurotoxicity through examining a translational biochemical weakness of common PD models. Neuromelanin is a pigmented byproduct of dopamine metabolism that has been debated as being both neurotoxic and neuroprotective in PD. Importantly, neuromelanin is known to bind and potentially release dopaminergic neurotoxicants, including HAAs (eg, β-carbolines such as harmane). Binding of other HAA subclasses (ie, aminoimidazoaazarenes) to neuromelanin has not been investigated, nor has a specific role for neuromelanin in mediating HAA-induced neurotoxicity been examined. Thus, we investigated the role of neuromelanin in modulating HAA-induced neurotoxicity. We characterized melanin from Sepia officinalis and synthetic dopamine melanin, proposed neuromelanin analogs with similar biophysical properties. Using a cell-free assay, we demonstrated strong binding of harmane and 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) to neuromelanin analogs. To increase cellular neuromelanin, we transfected SH-SY5Y neuroblastoma cells with tyrosinase. Relative to controls, tyrosinase-expressing cells exhibited increased neuromelanin levels, cellular HAA uptake, cell toxicity, and oxidative damage. Given that typical cellular and rodent PD models form far lower neuromelanin levels than humans, there is a critical translational weakness in assessing HAA-neurotoxicity. The primary impacts of these results are identification of a potential mechanism by which HAAs accumulate in catecholaminergic neurons and support for the need to conduct neurotoxicity studies in systems forming neuromelanin.